Cinematica del gas ionizado y perfiles de luminosidad de las Galaxias Porotos Verdes - Díaz, Rubén Joaquín (2013)
Abstract: We present preliminary spectroscopic results of a sample of green bean galaxies (GBG), known to show ultra luminous, galaxy-wide,narrow-line regions. We analyze Gemini GMOS-S,N spectra of a sample of 12 GBG in order to obtain emission line ratios, gas kinematics and luminosity profiles in some continuous bands. We report here new results that confirm that the [OIII]5008 emission extends from 5 to 17 kpc, in all cases scales similar or larger than the stellar continuums at the spectra. In the extreme case of J145533.6+044643 the [OIII] emission reaches a diameter of 17.51.6 kpc. We find that the continuum half light radii extend from 3 to 7 kpc, the largest scale radius at shortest wavelengths, which is consistent with the scale lengths of large spiral galaxies or merging systems. Another new result is that the spatial variation of the continuum color profiles indicate the presence of extinction and possibly star formation.